Tess of the d'Urbervilles : a pure woman - Hardy, Thomas, 1840-1928 (Penguin English library., 1978)
Tess struggles to overcome poverty and ignorance, but is no match for the wiles of various men, who use her and then condemn her. She is a classic tragic hero, good of heart but damned by society.